Cloning, purification and preliminary crystallographic analysis of a conserved hypothetical protein, SA0961 (YlaN), from Staphylococcus aureus - Xu, Ling (International Union of Crystallography, 2006)

(untitled)
SA0961 is an unknown hypothetical protein from Staphylococcus aureus that can be identified in the Firmicutes division of Gram-positive bacteria. The gene for the homologue of SA0961 in Bacillus subtilis, ylaN, has been shown to be essential for cell survival, thus identifying the protein encoded by this gene as a potential target for the development of novel antibiotics. SA0961 was cloned and the protein was overexpressed in Escherichia coli, purified and subsequently crystallized. Crystals of selenomethionine-labelled SA0961 diffract to beyond 2.4 Å resolution and belong to the monoclinic space group P2(1), with unit-cell parameters a = 31.5, b = 42.7, c = 62.7 Å, β = 92.4° and two molecules in the asymmetric unit. A full structure determination is under way to provide insights into the function of this protein.